Analisis pengaruh budaya organisasi dan kepuasan kerja terhadap turnover intention karyawan (Studi Pada Green Terrace Tegallalang, Gianyar - Bali) - Mahayasa, I Gede Aryana; Putra, I Gusti Ngurah Andika; Oktarini, Luh Nik (Implementasi Manajemen & Kewirausahaan, 2023)
Turnover intention is an employee's desire to leave an organization that has not been realized in a definite action to leave the organization where the employee is. The purpose of this study was to determine the effect of organizational culture and job satisfaction on turnover intention at Green Terrace Tegallalang. The number of respondents is 38 employees (saturated sampling). Data collection was carried out through observation, questionnaires, interviews, literature and documentation. The data analysis technique used is validity and reliability test, classical assumption test, multiple linear regression analysis, determination, t test (partial regression), and F test (simultaneous regression). The results found a negative and significant effect of organizational culture (X1) on employee turnover intention (Y). there is a negative and significant effect of job satisfaction (X2) on employee turnover intention (Y). there is a negative and significant effect of organizational culture (X1) and job satisfaction (X2) on employee turnover intention (Y) at Green Terrace Tegallalang. Keywords: Organizational Culture, Job Satisfaction and Turnover Intention